2015
DOI: 10.1002/bem.21903
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moderate intensity static magnetic fields on human bone marrow‐derived mesenchymal stem cells

Abstract: This study aimed to explore effects of static magnetic fields (SMFs) of moderate intensity (3-50 mT) as biophysical stimulators of proliferation and osteoblastic differentiation of human bone marrow-derived mesenchymal stem cells (MSCs). MSCs were exposed to SMFs of three intensities: 3, 15, and 50 mT. Proliferation was assessed by cell counting and bromodeoxyuridine incorporation, and differentiation by measuring alkaline phosphatase (ALP) activity, calcium content, mineralized nodule formation, and transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 39 publications
3
62
1
1
Order By: Relevance
“…To date, reports of SMF use with MSCs have demonstrated that moderate SMFs can have divergent effects (enhancing or inhibiting) on MSC viability [19, 45], proliferation [4547], differentiation capacity [19, 31, 47, 48], colony formation [31], and extracellular vesicle secretion [19, 46] (summarized in Table 2 and Fig. 2).…”
Section: Concernsmentioning
confidence: 99%
“…To date, reports of SMF use with MSCs have demonstrated that moderate SMFs can have divergent effects (enhancing or inhibiting) on MSC viability [19, 45], proliferation [4547], differentiation capacity [19, 31, 47, 48], colony formation [31], and extracellular vesicle secretion [19, 46] (summarized in Table 2 and Fig. 2).…”
Section: Concernsmentioning
confidence: 99%
“…Conversely, the positive effect of SMF (3–50 mT) on BMSCs has also been reported by Kim et al . (21). Until now, the resulting effect was considered to be associated with the cell type, time of exposure, and initial cell densities (22, 23).…”
Section: Resultsmentioning
confidence: 99%
“…A magnet was placed horizontally below the wells, and the north (N) side of magnet was oriented towards the well. We selected the same SMF intensities that were found to stimulate osteogenic differentiation in MSCs [Kim et al, ] and periodontium‐derived cells [Kim et al, ] in our previous studies. The SMFs were established by controlling the distance between the magnet and culture plates, as previously described [Kim et al, ; Kim et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that 15 mT intensity SMF, which is a relatively weak intensity among moderate SMF intensity ranges (1 mT–1 T), can trigger earlier peri‐implant bone formation than the absence of a magnetic field in vivo [Leesungbok et al, ; Kim et al, ]. Moreover, we demonstrated that 15 mT intensity SMFs could enhance the proliferation and osteogenic differentiation of human bone marrow‐derived mesenchymal stem cells (MSCs) [Kim et al, ] and periodontium‐derived cells, such as osteoblasts, cementoblasts, and periodontal ligament cells [Kim et al, ] in vitro. As osteoblastic stromal cells in physiological conditions modulate osteoclastogenesis and osteoclastic bone resorption [Takahashi et al, ], it is assumed that SMF‐induced osteogenic differentiation in osteoblasts would also affect osteoclasts.…”
Section: Introductionmentioning
confidence: 99%